1998
DOI: 10.1002/bbpc.19981020328
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of excited state deactivation paths in heteroazaaromatics with multiple intermolecular hydrogen bonds

Abstract: Transient absorption and luminescence studies were performed for several heteroazaaromatic molecules which possess both hydrogen bonding donor and acceptor groups, and which are capable of forming cyclic, double intermolecular hydrogen bonds. In protic solvents, these systems exhibit complex photophysics, manifested by a strong quenching of the fluorescence. In dipyrido[2,3‐a:3′,2′‐i]carbazole and 7,8,9,10‐tetrahydropyri‐do[2,3‐a]carbazole, photoinduced double proton transfer is observed in the first excited s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 71 publications
0
16
0
Order By: Relevance
“…However, our transient picosecond studies for pyridine solutions 42 have not detected the presence of any transient band in the visible region that could be assigned to a CT state. Also, no spectral changes were observed that would indicate a proton transfer along the hydrogen bond.…”
Section: Calculations and Analysis Of Excited-state Patternsmentioning
confidence: 61%
“…However, our transient picosecond studies for pyridine solutions 42 have not detected the presence of any transient band in the visible region that could be assigned to a CT state. Also, no spectral changes were observed that would indicate a proton transfer along the hydrogen bond.…”
Section: Calculations and Analysis Of Excited-state Patternsmentioning
confidence: 61%
“…In view of the above, it seemed instructive to investigate the photophysical characteristics of other bifunctional molecules related to 7AI . The properties of alcohol solvates of 1-azacarbazole ( 1AC ) appear to be similar to those of 7AI . On the other hand, large differences have been observed for a series of bifunctional azaheterocyclic compounds composed of indole, carbazole, or pyrrole hydrogen-bonding donors and of pyridine acceptor units. We have shown that the room temperature fluorescence of several methylene-bridged 2-(2‘-pyridyl)indoles is strongly quenched in alcohol solutions. , The quantum yields of fluorescence in alcohols are nearly 2 orders of magnitude lower than in aprotic polar and nonpolar solvents. This difference is observed only for molecules which possess both, the hydrogen bond donor, the NH group, and the hydrogen bond acceptor, the pyridine type nitrogen atom.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35] On the other hand, large differences have been observed for a series of bifunctional azaheterocyclic compounds composed of indole, carbazole, or pyrrole hydrogen-bonding donors and of pyridine acceptor units. [36][37][38][39][40][41][42] We have shown that the room temperature fluorescence of several methylene-bridged 2-(2′-pyridyl)indoles is strongly quenched in alcohol solutions. 36,37 The quantum yields of fluorescence in alcohols are nearly 2 orders of magnitude lower than in aprotic polar and nonpolar solvents.…”
Section: Introductionmentioning
confidence: 99%
“…To gain insight into the details of the photophysical processes initiated by hydrogen bonding, the effect of HFIP was examined in CH 2 The equilibrium constants of 1:1 (K 1 ) and 1:2 (K 2 ) complexes were calculated by global analysis of the experimental results in the 330-390 nm range. Since HFIP was added in a large excess compared to LuA, the absorbance change was described by the function: Addition of Zn(NO 3 ) 2 caused a similar spectral change, but the driving force of Zn 2+ complexation was significantly smaller than that of Cd 2+ .…”
Section: Effect Of Hydrogen Bonding In Ch 2 CLmentioning
confidence: 99%
“…[1][2][3][4][5][6] Light absorption of these species altered the charge density on the heteroatoms inducing considerable change in the acid-base strength. Consequently, photoinduced proton transfer or excited-state tautomerization could occur.…”
Section: Introductionmentioning
confidence: 99%